Testing the Pelletizing Capacity and Calorific Value of Fuel Briquettes from Agricultural Residues: การทดสอบความสามารถในการอัดแท่งและค่าความร้อนของเชื้อเพลิงอัดแท่งจากเศษเหลือทางการเกษตร - Muisee, Komsan; Janthasit, Krisana (Advanced Science Journal, 2023)
This research aimed to study the fuel capability of the agricultural residues included pineapple, durian and mangosteen rind to produce the charcoal briquette and fuel briquette. The materials were joined by using tapioca starch and formed the workpiece by the cold working process to achieve the community product standard. The results showed that the heat values of the charcoal briquette from durian, mangosteen and pineapple rind were 5,554, 5,888 and 4,951 kilocalories/kilogram, whereas the heat values of the green fuel from durian, mangosteen and pineapple rind were 4,079, 4,454 and 3,787 calories/gram, respectively. From the results, it is indicated that the agricultural residues could be added value by using to produce the charcoal and green fuel briquette. Agricultural waste can be produced as fuel briquettes. And charcoal briquettes the production process of fuel briquettes is shorter than the production process of charcoal briquettes resulting in lower costs. And lower heating value than charcoal briquettes